In‐tandem Electrochemical Reduction of Nitrate to Ammonia on Ultrathin‐Sheet‐Assembled Iron‐Nickel Alloy Nanoflowers - Chandra Majhi, Kartick; Chen, Hongjiang; Batool, Asma; Zhu, Qi; Jin, Yangxin; Liu, Shengqin; Sit, Patrick H.‐L.; Chun‐Ho Lam, Jason (Angewandte Chemie International Edition, 2025)
The development of alternative routes for ammonia (NH3) synthesis with high Faradaic efficiency (FE) is crucial for energy conservation and to achieve zero carbon emissions. Electrocatalytic nitrate (NO3−) reduction to NH3 (e‐NO3RRA) is a promising alternative to the energy‐intensive, fossil‐fuel‐driven Haber–Bosch process. The implementation of this innovative NH3 synthesis technique requires an efficient electrocatalyst and in‐depth mechanistic understanding of e‐NO3RRA. In this study, we developed an ultrathin sheet (μm) iron–nickel nanoflower alloy through electrodeposition and used it for e‐NO3RRA under alkaline conditions. The prepared Fe−Ni alloy exhibited an FE of 97.28±1.36 % at −238 mVRHE and an NH3 yield rate up to 3999.1±242.59 μg h−1 cm−2. Experimental electrolysis, in situ Raman spectroscopy, and density functional theory calculations showed that the adsorption and reduction of NO3− to NO2− occurred on the Fe surface, whereas subsequent hydrogenation of NO2− to NH3 occurred preferentially on the Ni surface. The catalysts exhibited comparable FE for at least 10 cycles, with a long‐term stability of 216 h. Electron paramagnetic resonance results confirmed that adsorbed hydrogen was consumed during e‐NO3RRA. This work introduces a sustainable, robust, and efficient Fe−Ni alloy electrocatalyst, offering an environmentally friendly approach for synthesizing NH3 from NO3−‐contaminated water. Electrochemical synthesis of an ultrathin‐sheet‐like nanoflower Fe−Ni (Fe80Ni20) alloy on a carbon cloth and electroreduction of NO3− to NH3 through an in‐tandem mechanism.